Barotrauma during non-invasive ventilation for acute respiratory distress syndrome caused by COVID-19: a balance between risks and benefits. (2nd June 2021) - Gabrielli, M; Valletta, F; Franceschi, F; ,
Abstract : Ventilatory support is vital for the management of severe forms of COVID-19. Non-invasive ventilation is often used in patients who do not meet criteria for intubation or when invasive ventilation is not available, especially in a pandemic when resources are limited. Despite non-invasive ventilation providing effective respiratory support for some forms of acute respiratory failure, data about its effectiveness in patients with viral-related pneumonia are inconclusive. Acute respiratory distress syndrome caused by severe acute respiratory syndrome-coronavirus 2 infection causes life-threatening respiratory failure, weakening the lung parenchyma and increasing the risk of barotrauma. Pulmonary barotrauma results from positive pressure ventilation leading to elevated transalveolar pressure, and in turn to alveolar rupture and leakage of air into the extra-alveolar tissue. This article reviews the literature regarding the use of non-invasive ventilation in patients with acute respiratory failure associated with COVID-19 and other epidemic or pandemic viral infections and the related risk of barotrauma.